DAYA SAING DAN LIBERALISASI PERDAGANGAN PADA INDUSTRI MANUFAKTUR INDONESIA - Bintang R.A. Majo Saibah; Nelvia Iryani; Syaiful Anwar (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
The manufacturing industry has a large contribution to the Indonesian economy, employment, and empowerment of human resources. But the development of the manufacturing industry also has challenges, where there are still many industries that have low competitiveness. This paper analyzes competitiveness by using a measure of labor productivity. Using data from Large Industrial Companies Medium in 2009-2012, this study analyzes the relationship of trade liberalization seen from economic openness in the form of the flow of goods and capital into the manufacturing industry sector to its productivity. The results of the study showed an increase in productivity with trade liberalization, besides that FDI Spillover Effects also occurred in the manufacturing industry in Indonesia.